Harmonic Suppressed Slot Antennas Using Rectangular/Circular Defected Ground Structures - Mohammad Saeid Ghaffarian; Gholamreza Moradi; Reza Zaker (International Journal of Antennas and Propagation)
Two wide rectangle-shaped microstrip-fed 2.6-GHz slot antennas using defected ground structures (DGSs) with a low design complexity are proposed to achieve wideband harmonic suppression. To accomplish this, two rectangular DGSs (RDGSs) in the first antenna and two circular DGSs (CDGSs) in the second one with various dimensions are etched into the ground plane, which could have a wideband-stop characteristic. Simulated and measured reflection coefficients indicate that the two proposed structures effectively suppress the second and third harmonics up to 23 dB between 3.5 and 10.5 GHz with a maximum ripple of 2.4 dB. In addition, the radiation patterns and peak gains of the antennas can be suppressed at least 17 dB and 7.1 dBi, respectively, at the third harmonic frequency of 7.86 GHz.